Minimization of Datasets : Using a Master Interlinked Dataset - Haider, Syed Ausaf; Patil, N. S. (Indian Journal of Computer Science, 2018)
We all know there are a lot of datasets. Each data set corresponds to the contents of a single statistical database. Datasets have several properties based on statistical measures applicable to the number and type of attributes or variables. Here, the focus is mainly on statistics i.e., sampling of data based on observation and analysis. Each data of a dataset is sampled quantitatively by doing binary encoding. Sampling of a dataset using a predictor can often result in error. However, these errors can have a trend that might be related to one or more datasets. This can differentiate every variable of one dataset from remaining datasets. All these datasets can be unified into a single master dataset based on user requirements.